INCONGRUITY AND DISPARAGEMENT HUMOR IN MR. BEAN'S NONVERBAL LANGUAGE - Nurhidayanto (UIN Raden Mas Said Surakarta, 2024)
This descriptive-qualitative research aimed to descriptively interpret Mr. Bean’s nonverbal language cues which fulfilled incongruity and disparagement humor. The method of analyzing the data was content analysis with input-process-output of analytical construct. The results of analysis reveal that Mr. Bean's gestures bring about movements that direct to implicature. From 88 units of analysis, there are found 62 fragments violating and only 4 fragments adhering to conventional meanings. Meanwhile, dealing with cooperative principles, there are 20 fragments violating and only 2 adhere to the principles. On the other hand, the nonverbal language cues demonstrated by Mr. Bean comprises gesture (88 times), facial expression (83), eye behavior (83), touching (28), posture (26), privacy (21), territory (21), distance (21), chronemics (9), space (8), artefactual (7), and bodily attractiveness (2). This study suggests that making humor through nonverbal language cues can provide benefits in creating a vivid learning atmosphere.